Implementation of Classroom Management and Infrastructure Management in Improving Learning Achievement - Raswati, Devi; Purnamaningsih, Ine Rahayu; Abduloh (Research Horizon, 2025)
This study is motivated by the importance of classroom management and the management of educational facilities and infrastructure in creating an effective learning environment that supports the improvement of elementary school students’ academic achievement. Well-managed learning conditions are believed to enhance student engagement, motivation, and learning outcomes. Therefore, this research aims to describe the implementation of classroom management and facilities management, as well as their contribution to improving students’ academic achievement in elementary schools in Pangkalan District. The study employs a qualitative approach with a case study design, involving teachers, school principals, and students as the main informants. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the Miles, Huberman, and Saldaña interactive model. The findings indicate that teachers have implemented classroom management through lesson planning, initial classroom conditioning, rule setting, and varied instructional strategies that support student engagement. School facilities are considered adequate, although unevenly distributed, and their utilization has been shown to increase students’ motivation and understanding. In conclusion, effective classroom management combined with supportive facilities significantly contributes to improving students’ academic achievement.